Testing English vocabulary - Řežábková, Petra (Univerzita Pardubice, 2011)
The thesis is aimed at design and usage of vocabulary tests with the involvement of various appropriate testing techniques as tools for gaining the positive backwash effect in the teaching/learning process.
Testování anglické slovní zásoby
Keywords: testování; slovní zásoba; testovací techniky; backwash efekt; testing; vocabulary; testing techniques